Big Data Analytic as the Foundation of Customer Retention - Asmoro, Anung; Edi Nugroho, Lukito; ., Selo (International Journal of Engineering and Technology, 2026)
Most companies spend energy and resources to build new business, but for companies have the customer base should its focus is trying in defending and improve relations with customers. This study aims to maintain telecommunications fixed broadband services customers in Indonesia based on big data analytic. This research result indicates the big data analytic can help predict customers that will terminate a relationship subscription. The implementation of the big data analytic produce a list of customers that is predicted will terminate a relationship with the company. Knowledge was used as a base to know the main cause of subscription and stop continued with business needs to be done to prevent it.